Exotic woody plants inclining to escape in the Buda Arboretum under strong urban effect in Budapest - Schmidt, G. (International Journal of Horticultural Science, 2001)
The Buda Arboretum of the Szent István University is situated in the western-middle part of the city of Budapest. It contains 1640 taxa of woody plants on an area of 7.5 ha. The sheltered position and the urban micro- and meso-climate is favourable for warm-loving, even subtropical plants, of which many species not simply stay alive, but flower, bear fruits and are spreading by seedlings in suitable spots. These instances call our attention to the possibilities that urban climate offers for landscapers, but also to over 110 species, which can be garden escapes in the future. Full list of plants, which tend to escape in the Arboretum is given in the paper.